Studying the influence of livestock pressure on gully erosion in rangelands of SW Spain by means of the UAV+SfM workflow - Álvaro Gómez Gutiérrez; Susanne Schnabel; Francisco Lavado Contador; José Juan de Sanjosé; Alan D. J. Atkinson; Manuel Pulido Fernández; Manuel Sánchez Fernández (Boletín de la Asociación de Geógrafos Españoles)
Gully erosion in agrosilvopastoral systems of SW Spain represents a common degradation process, but has been hardly analysed. The suitability of using the Unmanned Aerial Vehicles (UAV) and Structure from Motion photogrammetry (SfM) workflow to map small valley-bottom gullies in these landscapes was tested. The results showed centimetre-level accuracy. Observed strengths and limitations of the UAV+SfM workflow in the study areas are discussed. The resulting cartography allowed mapping soil erosion forms at outstanding spatial scales. All study areas showed evidences of degradation.